ОСНОВНІ РЕЖИМИ РОБОТИ І ГРАФІЧНИЙ ІНТЕРФЕЙС КОРИСТУВАЧА КОМПЛЕКСУ ДЛЯ ЕКСПЕРИМЕНТАЛЬНИХ ДОСЛІДЖЕНЬ МАГНІТНИХ ПОЛІВ І ДІАГНОСТУВАННЯ ЕЛЕКТРОЕНЕРГЕТИЧНОГО ОБЛАДНАННЯ - Мазманян, Р.О. (Інститут електродинаміки Національної академії наук України, 2024)
Hardware and software monitoring complex is designed to study the relationship between changes in the patterns of the magnetic field intensity distribution with power equipment failures. In experimental studies with predetermined technical faults artificially introduced into the object the complex will provide useful and reliable results by registering changes in the magnetic field induction in the spatial, temporal and frequency domains. The choice and flexible adjustment of data collection tools by the researcher will ensure the use of the most appropriate method for measuring, converting and displaying information about the investigated faults. The article presents the main operating modes and graphical user interfaces of a personal computer and a mobile data acquisition system that jointly convert, store, analyze and display measurement information received from various magnetic sensors. The generalized functional specification of the complex software, the design of the graphical user interface (GUI) as parts of the real-time operating system (RTOS) of the mobile data acquisition system (DAQ) and PC software will also be used in the development of problem-oriented computer diagnostic systems for electric power equipment. Ref 12., Fig. 3.